Enacting adolescent literacies across communities : Latino/a scribes and their rites - Rodríguez, Rodrigo Joseph (Lexington Books, 2017)
This book analyzes Latino/a adolescents' engagement with the elements of literacy for English language arts learning and understanding. How young people enact literacies in their bicultural lives and understand literary traditions today reveals their own interests in democracy, equity, and opportunity. Moreover, the rites they perform often recover buried histories, mirrors, and stories similar to the pre-Columbian scribes whose intellectual legacy is relevant in the twenty-first century. R. Joseph Rodríguez illustrates how adolescents experience scribal identities and language pluralism that sustains their cultural knowledge as they make meaning and enact literacies with diverse audiences in civic and schooling communities.